Cloning and Sequencing cDNA Encoding for Rhoptry-2 Toxoplasma Gondii Tachyzoite Local Isolate - Artama, Wayan T.; Sari, Yulia; Subekti, Didik Tulus; Poerwanto, Soenarwan Hery; Subandono, Jarot (Universitas Gadjah Mada, 2005)
Rhoptry protein belongs to an excretory and secretory antigens (ESAs) that play an important role during activepenetration of parasite into the cell target. This protein an able Toxoplasma gondii to actively penetrate targetedcell, meanwhile ESAs protein stimulates intracellular vacuole modification. It is, therefore, after the parasitesuccessfully enter the cell target then Granule (GRA) proteins are responsible for the formation of parasitophorusvacuole, which is protect the fusion with other intracellular compartments such as lysosomal vacuole. Consequently,this parasite is being able to survive and multiply at the cell target. The current study was aimed to clone andsequens cDNA encoding for ROP-2 of local isolated T. gondii tachizoite through DNA recombinant technique.Total ribonucleic acid (RNA) was isolated from tachyzoites of local isolated T. gondii that were grown up in Balb/c mice. Messenger RNA was isolated from total RNA using PolyAtract mRNA Isolation System. Messenger RNA wasused as a template for synthesis cDNA using Riboclone cDNA Synthesis System AMV-RT. EcoRI adaptor fromRiboclone EcoRI Adaptor Ligation System was added to Complementary DNA and than ligated to pUC19. Recombinantplasmid was transformed into E. coli (XL1-Blue). The transformed E. coli XL-1 Blue were plated on LB agarcontaining X-Gal, IPTG and ampicillin. Recombinant clones (white colony) were picked up and grown up in theLB medium at 37oC overnight. Expression of recombinant protein was analysed by immunoblotting in order toidentify cDNA recombinant wich is express ESA of T. gondii local isolate. Recombinant plasmid were isolatedusing alkalilysis method and were elektroforated in 1% agarose gel. The isolated DNA recombinant plasmid wascut using Eco RI and then sequenced through Big Dye Terminator Mix AB1 377A Sequencer using M13 Forward andM13 Reverse primers. The conclusion of this results showed that the recombinant clone was coding for excretoryand secretory protein which has molecular weight of 54 kDa. The DNA alignments of sequence from the clonedgene showed 97% homology with gene encoding for ROP-2 of T. gondii RH isolate.Keywords: Toxoplasma gondii, tachizoite, ESA, complementary DNA, ROP2